Analysis on the Legal Force of Copyright Registration Document as Evidence of Ownership of Indigenous Land - Christina Ella Yonatan; Xavier Nugraha (Universitas Airlangga, 2021)
Registration of copyright patent or registration is a letter approved and issued by the Ministry of Law and Human Rights for copyright. To protect the rights to indigenous land, the Moi tribal community has registered 2 (two) registrations that have been issued by the Ministry of Law and Human Rights, including 1) Registration of copyright with types of creation: Database and title of work: Results of the Open and Close Tribe Meeting with the head of the Tribe Council of Malamoi Sorong and Indigenous Peoples of the Moi Tribe on the Status of Indigenous Land Ownership in the Sorong City Government Area on behalf of the Malibela Klawalu clan, the Kalagison Milo clan, the Mubalus clan, the Kalawaisa clan, the Bawela Mubalus clan, the Osok Malaimsimsa clan. , Marga Kalami Klaglas Klaglas On 10 April 2013. 2). Letter of Registration of copyright with the type of copyrights: Map of the 7 Boundary of the Moi Indigenous Land Owners in the Sorong City Area. Based on the document, the Moi tribal community used it as a basis to claim the lands in the Sorong City government territory were the indigenous land belonging to the Moi tribe. This study uses a statutory and conceptual approach. The results of this study are that the registration document does not have legal force as evidence to prove ownership of indigenous land rights. A letter of registration remains important if there are legal issues with copyright in the future. The document can be used as initial evidence to determine who has the rights to the subject or the copyright holder or ones who is more entitled to the subject.